Kant’s Critique of the Principles of Rationalist Metaphysics: The Pre-Critical Concept of «Real Possibility» - Segesta, Jessica (Con-Textos Kantianos. International Journal of Philosophy, 2024)
The aim of this essay is to highlight the ontological reasons of Kant’s critique of rationalist metaphysics. More specifically, we will show that Kant’s critique of the principle of non-contradiction calls into question the notion of possibility on which rationalist ontology was based. By analyzing some passages from the Nova Dilucidatio and the Beweisgrund to the light of some the theses from the Metaphysik Herder, we will show that at the core of Kant’s metaphysical conception of these years lies a notion of the possible that is consistent with the thesis of the pre-predicative character of existence as well as with the reassessment of the real value of spatio-temporal determination.